1996
DOI: 10.2337/diab.45.12.1678
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally Expressed Low-Voltage-Activated Calcium Channels in β-Cells From NOD Mice and a Related Clonal Cell Line

Abstract: A macroscopic low-voltage-activated (LVA) inward current was found in pancreatic beta-cells isolated from NOD mice. However, this current was not present in nondiabetic prone mouse (e.g., Swiss-Webster) pancreatic beta-cells. We performed pharmacological analyses on this current in NOD insulinoma tumor cells (NIT-1). This cell line was developed from pancreatic beta-cells of a transgenic NOD mouse. The sodium-channel blocker, tetrodotoxin (TTX; 2 micromol/l) had no effect on this LVA current. The amplitudes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Similar studies using the rat insulinoma cell line INS-1 found that low concentrations of nickel could completely block T-type currents (IC 50 ϭ 30 M) and partially block insulin secretion (42). Nickelsensitive T-type currents (IC 50 ϭ 3 M) have also been recorded from the mouse insulinoma cell line NIT-1 (426). Li and co-workers (463) also cloned a splice variant of Ca v 3.1 from an INS-1 cDNA library.…”
Section: Pancreasmentioning
confidence: 59%
See 3 more Smart Citations
“…Similar studies using the rat insulinoma cell line INS-1 found that low concentrations of nickel could completely block T-type currents (IC 50 ϭ 30 M) and partially block insulin secretion (42). Nickelsensitive T-type currents (IC 50 ϭ 3 M) have also been recorded from the mouse insulinoma cell line NIT-1 (426). Li and co-workers (463) also cloned a splice variant of Ca v 3.1 from an INS-1 cDNA library.…”
Section: Pancreasmentioning
confidence: 59%
“…427). However, the I-V curve for the cytokine-induced current peaked between ϩ10 and ϩ20, while under similar recording conditions this group found that bona fide, slowly deactivating, T-type currents peaked between Ϫ20 and Ϫ10 mV (426). Human ␤-cells express both LVA and HVA currents, and in 20% of the cells tested, the LVA current was dominant (25).…”
Section: Pancreasmentioning
confidence: 83%
See 2 more Smart Citations
“…Because recent articles reported the expression of the LVA-Ca 2ϩ channel in islet ␤ cells from NOD mice (25) and activation of the LVA-Ca 2ϩ channel in pancreatic islet cell death by cytokines (16), we first studied whether LVA-Ca 2ϩ channel was activated in our model of pancreatic islet cell death by 100 U/ml IFN-␥ in combination with 10 ng/ml TNF-␣ (IFN-␥/TNF-␣) using MIN6N8 insulinoma cells. Under the whole-cell patch clamp condition, an inward Ca 2ϩ current appeared at above Ϫ40 mV and reached its peak at 0 mV.…”
Section: Increased Ca 2ϩ Flux and Intracellular Ca 2ϩ Contents By Ifnmentioning
confidence: 99%